2015
DOI: 10.1038/sc.2015.41
|View full text |Cite
|
Sign up to set email alerts
|

Functional hindrance due to spasticity in individuals with spinal cord injury during inpatient rehabilitation and 1 year thereafter

Abstract: Study design: Prospective cohort study. Objective: To assess functional hindrance due to spasticity during inpatient rehabilitation and 1 year thereafter in individuals with spinal cord injury (SCI) and to determine factors that influence the hindrance. Setting: Eight specialized rehabilitation centres in the Netherlands. Methods: A total of 203 patients with recent SCI rated the hindrance they perceived due to spasticity in daily living at the start of active rehabilitation (t1), 3 months later (t2), at disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
(23 reference statements)
0
9
1
Order By: Relevance
“…While there was a significant increase in both the percentage of individuals with spasticity and the average reported severity of spasticity, there was no significant change in the percentage of individuals who used prescription medications for spasticity. We found that the majority of individuals (~55%) took prescription medications for spasticity, slightly higher than previous findings, which estimate 35-46% of persons with chronic SCI use prescription medications (e.g., baclofen, dantrolene, diazepam, or tizanidine) to manage their symptoms [6,17,19,23]. Considering the frequency of use, we found that roughly 9% of participants took their medications only sometimes or weekly.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…While there was a significant increase in both the percentage of individuals with spasticity and the average reported severity of spasticity, there was no significant change in the percentage of individuals who used prescription medications for spasticity. We found that the majority of individuals (~55%) took prescription medications for spasticity, slightly higher than previous findings, which estimate 35-46% of persons with chronic SCI use prescription medications (e.g., baclofen, dantrolene, diazepam, or tizanidine) to manage their symptoms [6,17,19,23]. Considering the frequency of use, we found that roughly 9% of participants took their medications only sometimes or weekly.…”
Section: Discussioncontrasting
confidence: 62%
“…Only a handful of prospective studies have assessed changes in spasticity, primarily focused on the first few years after injury [15,19,22,23]. In some studies, the prevalence was reported to decrease over time [18,[20][21][22], while others have found the odds of reporting spasticity to increase over time [24].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the reduction of spasticity, we previously reported a decrease of mAs after HAL gait training for a patient with C4 SCI (Ikumi et al, 2017 ). Spasticity negatively influences quality of life for many SCI patients by causing pain, joint contracture, and restricted activity of daily living (Adams and Hicks, 2005 ; van Cooten et al, 2015 ). Therefore, this method may be useful to reduce spasticity and related concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Spasticity is present in about 65% of patients with a traumatic spinal cord injury (SCI) at the time of rehabilitation discharge (Holtz et al, 2017) and increasing over time to 85% (Jorgensen et al, 2017;DiPiro et al, 2018). About 35-55% of SCI patients take some antispasticity medication (Holtz et al, 2017;DiPiro et al, 2018) and the majority report that the spasticity negatively affects daily functioning (van Cooten et al, 2015) and quality of life (Adams and Hicks, 2005). Many treatments exist for spasticity, including physical therapy modalities, pharmacological interventions, botulinum toxin injections, intrathecal drug delivery, and finally, surgery (Elbasiouny et al, 2010).…”
Section: Introductionmentioning
confidence: 99%